Light speed expanding reversed black hole quantum cosmology - V. S. Seshavatharam, U; Lakshminarayana, S (International Journal of Advanced Astronomy, 2018)
With reference to ordinary matter, dark matter, critical density and time reversed black hole physics, it seems possible to develop a model of light speed quantum cosmology.Â